Hydrogenation catalyst film-forming flame retardant, method for preparing same, and use thereof

By using a hydrogenation catalyst film-forming flame retardant with oxygen-containing hydrocarbons, cross-linked grafted nano-silica, and anionic surfactants, the problems of spontaneous combustion and poor permeability of hydrogenation catalysts were solved, achieving safe unloading and improved stability of the catalyst.

CN120961238BActive Publication Date: 2026-01-16山东昊瑞环保科技有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511496890.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-01-16
Estimated Expiration
2045-10-20

AI Technical Summary

Technical Problem

Existing hydrogenation catalysts are prone to spontaneous combustion during the unloading process, and the flame retardant composition cannot quickly penetrate into the agglomerated catalyst during the unloading process, resulting in poor uniformity and density of the passivation film.

Method used

A hydrogenation catalyst film-forming flame retardant composed of oxygen-containing hydrocarbons, cross-linked grafted nano-silica, anionic surfactants, and co-solvents is used to form a uniform and dense passivation film on the catalyst surface through cross-linked grafted nano-silica, thereby improving the permeability.

Benefits of technology

This achieves rapid penetration and uniform coverage of the hydrogenation catalyst, improving the safety of the unloading process and the stability of the catalyst, and reducing the risk of equipment corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application belongs to the technical field of catalyst unloading protection, and particularly relates to a hydrogenation catalyst film-forming flame retardant, a preparation method and application thereof, which comprises the following components in parts by weight: oxygen-containing hydrocarbon 90-95 parts, crosslinked grafted nano-silicon dioxide 1-5 parts, anionic surfactant 5-10 parts, dispersant 0.5-1 part and cosolvent 5-10 parts. In the application, the crosslinked grafted nano-silicon dioxide is dispersed in the oxygen-containing hydrocarbon to form a nano-fluid, the permeability of the film-forming flame retardant is improved, the film-forming flame retardant rapidly penetrates into the inside of the caked catalyst, and a more uniform and dense passivation film is formed.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of catalyst unloading protection, and particularly relates to a hydrogenation catalyst film-forming flame retardant, a preparation method and application thereof. BACKGROUND

[0002] Fixed-bed hydrogenation catalysts such as hydrocracking and hydrofining catalysts mostly contain metals such as nickel, cobalt, molybdenum, tungsten and iron, and these metals are generally in a highly sulfidized state after reaction, and the presence of coke makes these catalysts extremely easy to self-ignite. If the catalyst is not effectively pretreated or protected after reaction, the metal sulfides are extremely easy to self-ignite during catalyst unloading.

[0003] A kind of hydrogenation catalytic flame-retardant composition and its use method with publication number CN112871219A include 100 parts of flame retardant, 5-15 parts of film-forming aid and 5-10 parts of cosolvent. By mixing the flame retardant and the film-forming aid in the cosolvent first, when added to the mixed oil of diesel and wax oil etc. in the hydrogenation reactor, it can be quickly compatible, promote the dispersion of the flame retardant and the film-forming aid, synergize with the mixed oil, improve the film-forming rate on the catalyst, form a passivation film at 170℃, and improve the unloading efficiency.

[0004] However, at the end of the device operation, the catalyst in the reactor is easy to caking, the above-mentioned flame-retardant composition cannot quickly penetrate into the inside of the caked catalyst, and the uniformity and density of the passivation film formed are low. SUMMARY

[0005] The purpose of the present application is to provide a hydrogenation catalyst film-forming flame retardant, a preparation method and application thereof to solve the above technical problems.

[0006] To achieve the above technical purpose, the technical solution of the present application is as follows:

[0007] A hydrogenation catalyst film-forming flame retardant, by weight fraction, includes the following components: oxygen-containing hydrocarbon 90-95 parts, crosslinked grafted nano-silica 1-5 parts, anionic surfactant 5-10 parts, dispersant 0.5-1 part and cosolvent 5-10 parts.

[0008] As a further improvement, the crosslinked grafted nano-silica is obtained by grafting polymer on the surface of 3-aminopropyl triethoxysilane modified silica nanoparticles with sodium allyloxyhydroxypropyl sulfonate and benzotriazole-methyl methacrylate as monomers.

[0009] As a further improvement, the oxygen-containing hydrocarbon is a higher aliphatic alcohol containing 12-18 carbon atoms, the dispersant is a higher alcohol, the anionic surfactant is an alkyl sulfonate, and the cosolvent is diesel or wax oil.

[0010] The application also provides a preparation method of the hydrogenation catalyst film-forming flame retardant, comprising the following steps:

[0011] S1, the 3-aminopropyl triethoxysilane modified silica nanoparticles are added to deionized water, ultrasonic dispersion is uniformly carried out, heating is carried out to 50~55 DEG C, the polymer monomer allyloxy hydroxypropyl sodium sulfonate and benzotriazole-methyl methacrylate are added to the mixture, then the initiator ammonium persulfate is added, after continuous stirring for 10 min, the reaction is continuously carried out under sealed conditions for 4~5 h, after the reaction is completed, the precipitate is separated by adding acetone, the precipitate is separated by centrifugation, and after washing and drying, the crosslinked grafted nanosilica is obtained;

[0012] S2, the oxygen-containing hydrocarbon, the crosslinked grafted nanosilica, the surfactant and the dispersant are added to the cosolvent at 60~65 DEG C, after mixing, stirring is carried out for 30 min, and the hydrogenation catalyst film-forming flame retardant is obtained.

[0013] As a further improvement, in step S1, the preparation method of the 3-aminopropyl triethoxysilane modified silica nanoparticles is as follows: the nanosilica is added to anhydrous ethanol, and stirring dispersion is carried out at room temperature to obtain a nanosilica dispersion liquid;

[0014] The 3-aminopropyl triethoxysilane and water are mixed in a volume ratio of 1:2, and stirring is carried out to obtain a silane coupling agent aqueous solution;

[0015] The silane coupling agent aqueous solution is poured into the nanosilica dispersion liquid, stirring is carried out, reaction is carried out at 70~75 DEG C for 3 h, after the reaction is completed, the precipitate is separated by centrifugation, and after washing and drying, the 3-aminopropyl triethoxysilane modified silica nanoparticles are obtained.

[0016] As a further improvement, the solid-liquid ratio of the nanosilica and the 3-aminopropyl triethoxysilane is 1 g:5 mL.

[0017] As a further improvement, in step S1, the preparation method of the benzotriazole-methyl methacrylate is as follows: the 1-hydroxymethyl benzotriazole, triethylamine and butanone are mixed, the methyl acryloyl chloride butanone solution is slowly added to the mixture, reaction is carried out at 0~10 DEG C for 2 h, then reaction is carried out at 22~25 DEG C for 5 h, after the reaction is completed, the solid substance is removed by filtration, the obtained solution is rotary evaporated, then ether is added, then the solution is washed with a sodium hydroxide solution and distilled water, the solid substance is removed by drying with anhydrous sodium sulfate, and the benzotriazole-methyl methacrylate is obtained after rotary evaporation.

[0018] As a further improvement, the molar ratio of the 1-hydroxymethyl benzotriazole and the methyl acryloyl chloride is 1~1.25:1, and the addition amount of the triethylamine is 30% of the total molar amount of the 1-hydroxymethyl benzotriazole and the methyl acryloyl chloride.

[0019] As a further improvement, in step S1, the molar ratio of the sodium allyloxyhydroxypropyl sulfonate, benzotriazole-methyl methacrylate is 1:1~1.02, the ratio of the mass of the 3-aminopropyl triethoxysilane modified silica nanoparticles to the total mass of the sodium allyloxyhydroxypropyl sulfonate and benzotriazole-methyl methacrylate is 1:5, and the mass of the initiator ammonium persulfate is 20% of the total mass of the sodium allyloxyhydroxypropyl sulfonate and benzotriazole-methyl methacrylate.

[0020] The application also provides the use of the hydrogenation catalyst film-forming flame retardant for catalyst protection during catalyst unloading of a hydrogenation device, and the hydrogenation device is any one of a fixed-bed residual oil hydrogenation device, a fixed-bed wax oil hydrogenation device, a fixed-bed hydrocracking device, a fixed-bed diesel oil hydrogenation device, a fixed-bed diesel oil reforming device, a fixed-bed kerosene hydrogenation device, a fixed-bed gasoline hydrogenation device, a fixed-bed gasoline hydro-upgrading device, a fixed-bed naphtha hydrogenation device, and a fixed-bed coal tar hydrogenation device.

[0021] Due to the adoption of the above technical solutions, the application has the following beneficial effects:

[0022] The application provides a hydrogenation catalyst film-forming flame retardant, a preparation method and application thereof, crosslinked grafted nano-silica is dispersed in oxygen-containing hydrocarbons to form a nanofluid, the permeability of the film-forming flame retardant is improved, the film-forming flame retardant can quickly penetrate into the inside of the caked catalyst, and a more uniform and dense passivation film is formed.

[0023] The sodium allyloxyhydroxypropyl sulfonate and the benzotriazole-methyl methacrylate are used as polymerization monomers, and the 3-aminopropyl triethoxysilane modified silica nanoparticles are crosslinked and grafted, the sodium allyloxyhydroxypropyl sulfonate can improve the wetting capacity of the nanofluid to the surface of the catalyst, ensure that the film-forming flame retardant uniformly covers the catalyst, and realize more uniform and dense wrapping of the catalyst, and the benzotriazole-methyl methacrylate can reduce the corrosion to the hydrogenation catalytic equipment. DETAILED DESCRIPTION

[0024] The technical solutions of the application will be described clearly and completely in combination with specific embodiments, but those skilled in the art will understand that the following described embodiments are part of the embodiments of the application, rather than all the embodiments, and are only used to illustrate the application, and should not be regarded as limiting the scope of the application. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor belong to the scope of protection of the application. The specific conditions are not indicated in the embodiments, and the conventional conditions or the conditions recommended by the manufacturer are used. The reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be purchased on the market.

[0025] In the present application, the specific structure of the alkyl sulfonate and the higher alcohol is not limited, the alkyl sulfonate used in the present application as an anionic surfactant is the prior art, and the higher alcohol used in the present application as a dispersant is also the prior art, therefore, the specific structure of the alkyl sulfonate and the higher alcohol is not limited.

[0026] Example 1 A hydrogenation catalyst film-forming flame retardant, by weight fraction, comprising the following components: dodecanol 90 parts, crosslinked grafted nano-silica 1 part, anionic surfactant alkyl sulfonate 5 parts, dispersant higher alcohol 0.5 parts and cosolvent diesel oil 5 parts.

[0027] In the present embodiment, the crosslinked grafted nano-silica is obtained by grafting polymer on the surface of silica nanoparticles modified by 3-aminopropyl triethoxysilane using sodium allyloxy hydroxypropyl sulfonate and benzotriazole-methyl methacrylate as monomers, and the specific preparation method is described in the preparation method of the hydrogenation catalyst film-forming flame retardant.

[0028] The present embodiment also provides a preparation method of the above-mentioned hydrogenation catalyst film-forming flame retardant, specifically comprising the following steps:

[0029] S1, 1g of nano-silica is added to 30mL of anhydrous ethanol, and stirred and dispersed at room temperature to obtain a nano-silica dispersion liquid;

[0030] 5mL of 3-aminopropyl triethoxysilane and 10mL of water are mixed to obtain a silane coupling agent aqueous solution;

[0031] The silane coupling agent aqueous solution is poured into the nano-silica dispersion liquid, and stirred and mixed, and reacted at 70℃ for 3h, and after the reaction is completed, the precipitate is separated by centrifugation, washed with ethanol, and then vacuum dried at 70℃ to obtain 3-aminopropyl triethoxysilane modified silica nanoparticles;

[0032] S2, 4.18g (0.04mol) of methacryloyl chloride and 20mL of butanone are mixed to obtain a methacryloyl chloride butanone solution;

[0033] 7.45g (0.05mol) of 1-hydroxymethyl benzotriazole, 3.04g (0.03mol) of triethylamine and 100mL of butanone are mixed, and the methacryloyl chloride butanone solution is added thereto, and reacted at 0℃ for 2h, and then reacted at 22℃ for 5h, and after the reaction is completed, the solid material is removed by filtration, and the obtained solution is rotary evaporated to remove butanone at 45℃, 200mbar and 150rpm, and then 50mL of diethyl ether is added to the obtained concentrated solution, and then washed with a 5% by mass sodium hydroxide solution and distilled water, and dried with anhydrous sodium sulfate, and the solid material is removed, and the solvent is rotary evaporated at 25℃, 200mbar and 120rpm to obtain benzotriazole-methyl methacrylate.

[0034] S3, 0.87g 3-aminopropyl triethoxysilane modified silica nanoparticles were added to 100g deionized water, and after ultrasonic dispersion, heated to 50℃, 2.18g (0.01mol) of polymer monomer allyloxy hydroxypropyl sulfonic acid sodium, 2.17g (0.01mol) of benzotriazole-methyl methacrylate were added, then 0.87g initiator ammonium persulfate was added, stirring for 10min, then continue to react for 4h under sealed condition, after the reaction was completed, 100mL acetone was added to the reaction system, the precipitate was separated by centrifugation at 5000r / min, and the precipitate was washed with ethanol for 3 times, and vacuum dried at 60℃ to obtain crosslinked grafted nano silica;

[0035] S4, dodecanol, crosslinked grafted nano silica, anionic surfactant alkyl sulfonate, dispersant higher alcohol were added to the cosolvent diesel at 60℃, mixed and stirred for 30min to obtain a hydrogenation catalyst film forming flame retardant.

[0036] The embodiment also provides catalyst protection of the hydrogenation catalyst film forming flame retardant when the hydrogenation device is unloaded, and the hydrogenation device is any one of a fixed bed residual oil hydrogenation device, a fixed bed wax oil hydrogenation device, a fixed bed hydrocracking device, a fixed bed diesel hydrogenation device, a fixed bed diesel oil modification device, a fixed bed kerosene hydrogenation device, a fixed bed gasoline hydrogenation device, a fixed bed gasoline hydrogenation modification device, a fixed bed naphtha hydrogenation device, and a fixed bed coal tar hydrogenation device.

[0037] Example 2: A hydrogenation catalyst film forming flame retardant, including the following components in parts by weight: tridecanol 95 parts, crosslinked grafted nano silica 5 parts, anionic surfactant alkyl sulfonate 10 parts, dispersant higher alcohol 1 part, and cosolvent wax oil 10 parts.

[0038] In the embodiment, the crosslinked grafted nano silica is obtained by grafting polymer on the surface of 3-aminopropyl triethoxysilane modified silica nanoparticles with allyloxy hydroxypropyl sulfonic acid sodium and benzotriazole-methyl methacrylate as monomers, and the specific preparation method is described in the preparation method of the hydrogenation catalyst film forming flame retardant.

[0039] The embodiment also provides a preparation method of the hydrogenation catalyst film forming flame retardant, which specifically includes the following steps:

[0040] S1, 1g of nano silica was added to 30mL of anhydrous ethanol, and dispersed by stirring at room temperature to obtain a nano silica dispersion;

[0041] 5mL of 3-aminopropyl triethoxysilane and 10mL of water were mixed and stirred to obtain a silane coupling agent aqueous solution;

[0042] The silane coupling agent aqueous solution was poured into the nanosilica dispersion liquid, mixed and stirred, and reacted at 75℃ for 3h. After the reaction was completed, the precipitate was separated by centrifugation, washed with ethanol, and then vacuum dried at 70℃ to obtain 3-aminopropyl triethoxysilane modified silica nanoparticles;

[0043] S2, 4.18g (0.04mol) of methacryloyl chloride was mixed with 20mL of butanone to obtain a butanone solution of methacryloyl chloride;

[0044] 5.96g (0.04mol) of 1-hydroxymethyl benzotriazole, 2.43g (0.024mol) of triethylamine and 100mL of butanone were mixed, and the butanone solution of methacryloyl chloride was added thereto. The reaction was carried out at 10℃ for 2h, and then at 25℃ for 5h. After the reaction was completed, the solid material was removed by filtration. The obtained solution was rotary evaporated at 45℃, 200mbar and 150rpm to remove butanone. Then 50mL of ether was added to the obtained concentrated solution, which was washed with a 5% mass fraction sodium hydroxide solution, distilled water, dried with anhydrous sodium sulfate, and then the solid material was removed. The solvent was removed by rotary evaporation at 25℃, 200mbar and 120rpm to obtain benzotriazole-methyl methacrylate;

[0045] S3, 0.87g of 3-aminopropyl triethoxysilane modified silica nanoparticles was added to 100g of deionized water, and then uniformly dispersed by ultrasonic. The mixture was heated to 55℃, and then 2.18g (0.01mol) of allyloxy hydroxypropyl sulfonic acid sodium, 2.21g (0.0102mol) of benzotriazole-methyl methacrylate were added thereto. Then 0.87g of initiator ammonium persulfate was added, and the mixture was continuously stirred for 10min. Then the reaction was continuously carried out under sealed condition for 5h. After the reaction was completed, 100mL of acetone was added to the reaction system, and the precipitate was separated by centrifugation at 5000r / min. The precipitate was washed with ethanol for 3 times, and then vacuum dried at 60℃ to obtain crosslinked grafted nanosilica.

[0046] S4, tridecanol, crosslinked grafted nanosilica, anionic surfactant alkyl sulfonate, dispersant higher alcohol were added to a cosolvent diesel oil at 65℃, and then mixed and stirred for 30min to obtain a hydrogenation catalyst film forming flame retardant.

[0047] Example 3 A hydrogenation catalyst film forming flame retardant, by weight fraction, includes the following components: tridecanol 92 parts, crosslinked grafted nanosilica 2 parts, anionic surfactant alkyl sulfonate 7 parts, dispersant higher alcohol 0.7 parts, and cosolvent diesel oil 7 parts.

[0048] In this embodiment, the crosslinked grafted nanosilica is obtained by grafting polymer on the surface of 3-aminopropyl triethoxysilane modified silica nanoparticles using sodium allyloxyhydroxypropyl sulfonate and benzotriazole-methyl methacrylate as monomers. The preparation method is described in the preparation method of the hydrogenation catalyst film-forming flame retardant.

[0049] The embodiment also provides the preparation method of the hydrogenation catalyst film-forming flame retardant, which specifically comprises the following steps:

[0050] S1, 1g of nanosilica is added to 30mL of anhydrous ethanol, and the nanosilica dispersion is obtained by stirring and dispersing at room temperature;

[0051] 5mL of 3-aminopropyl triethoxysilane and 10mL of water are mixed to obtain a silane coupling agent aqueous solution;

[0052] The silane coupling agent aqueous solution is poured into the nanosilica dispersion, and stirred and mixed, and then reacted at 73℃ for 3h. After the reaction is completed, the precipitate is separated by centrifugation, washed with ethanol, and then dried at 70℃ under vacuum to obtain 3-aminopropyl triethoxysilane modified silica nanoparticles;

[0053] S2, 4.18g (0.04mol) of methacryloyl chloride and 20mL of butanone are mixed to obtain a methacryloyl chloride butanone solution;

[0054] 6.56g (0.044mol) of 1-hydroxymethyl benzotriazole, 2.53g (0.025mol) of triethylamine and 100mL of butanone are mixed, and the methacryloyl chloride butanone solution is added thereto, and then reacted at 5℃ for 2h and at 23℃ for 5h. After the reaction is completed, the solid substance is removed by filtration, and the obtained solution is rotary evaporated to remove butanone at 45℃, 200mbar and 150rpm. Then, 50mL of diethyl ether is added to the obtained concentrated solution, and then washed with a 5% by mass sodium hydroxide solution and distilled water. After drying with anhydrous sodium sulfate, the solid substance is removed, and the solvent is rotary evaporated at 25℃, 200mbar and 120rpm to obtain benzotriazole-methyl methacrylate;

[0055] S3, 0.87g 3-aminopropyl triethoxysilane modified silica nanoparticles were added into 100g deionized water, after ultrasonic dispersion, heated to 53℃, then 2.18g (0.01mol) polymer monomer allyloxy hydroxypropyl sulfonic acid sodium, 2.19g (0.0101mol) benzotriazole-methyl methacrylate were added, then 0.87g initiator ammonium persulfate was added, stirring for 10min, then continue to react for 4.5h under sealed condition, after reaction, 100mL acetone was added into the reaction system, precipitate was separated by centrifugation at 5000r / min, then washed with ethanol for 3 times, dried at 60℃ under vacuum to obtain crosslinked grafted nano silica;

[0056] S4, tetradecanol, crosslinked grafted nano silica, anionic surfactant alkyl sulfonate, dispersant higher alcohol were added into 62℃ cosolvent diesel, mixed and stirred for 30min to obtain hydrogenation catalyst film forming flame retardant.

[0057] Example 4, a hydrogenation catalyst film forming flame retardant, by weight fraction, includes the following components: pentadecanol 93 parts, crosslinked grafted nano silica 3 parts, anionic surfactant alkyl sulfonate 8 parts, dispersant higher alcohol 0.8 parts and cosolvent diesel 8 parts.

[0058] In this embodiment, the crosslinked grafted nano silica is obtained by grafting polymer on the surface of 3-aminopropyl triethoxysilane modified silica nanoparticles with allyloxy hydroxypropyl sulfonic acid sodium and benzotriazole-methyl methacrylate as monomers, and the specific preparation method is described in the preparation method of hydrogenation catalyst film forming flame retardant.

[0059] The preparation method of the hydrogenation catalyst film forming flame retardant of this embodiment is the same as that of example 1, and the only difference is that the mass fraction of each component is different.

[0060] Example 5, a hydrogenation catalyst film forming flame retardant, by weight fraction, includes the following components: hexadecanol 94 parts, crosslinked grafted nano silica 4 parts, anionic surfactant alkyl sulfonate 9 parts, dispersant higher alcohol 0.9 parts and cosolvent diesel 9 parts.

[0061] In this embodiment, the crosslinked grafted nano silica is obtained by grafting polymer on the surface of 3-aminopropyl triethoxysilane modified silica nanoparticles with allyloxy hydroxypropyl sulfonic acid sodium and benzotriazole-methyl methacrylate as monomers, and the specific preparation method is described in the preparation method of hydrogenation catalyst film forming flame retardant.

[0062] The preparation method of the hydrogenation catalyst film forming flame retardant of this embodiment is the same as that of example 1, and the only difference is that the mass fraction of each component is different.

[0063] Example 6 A hydrogenation catalyst film-forming flame retardant, by weight parts, comprising the following components: heptadecanol 91 parts, crosslinked grafted nano-silica 2 parts, anionic surfactant alkyl sulfonate 6 parts, dispersant higher alcohol 0.6 parts and cosolvent diesel 6 parts.

[0064] In this embodiment, the crosslinked grafted nano-silica is obtained by grafting polymer on the surface of 3-aminopropyl triethoxysilane modified silica nanoparticles with sodium allyloxy hydroxypropyl sulfonate and benzotriazole-methyl methacrylate as monomers, and the specific preparation method is described in the preparation method of the hydrogenation catalyst film-forming flame retardant.

[0065] The preparation method of the hydrogenation catalyst film-forming flame retardant of this embodiment is the same as that of Example 1, and the only difference is that the mass fractions of the components are different.

[0066] Example 7 A hydrogenation catalyst film-forming flame retardant, by weight parts, comprising the following components: octadecanol 93 parts, crosslinked grafted nano-silica 3 parts, anionic surfactant alkyl sulfonate 8 parts, dispersant higher alcohol 0.8 parts and cosolvent diesel 8 parts.

[0067] In this embodiment, the crosslinked grafted nano-silica is obtained by grafting polymer on the surface of 3-aminopropyl triethoxysilane modified silica nanoparticles with sodium allyloxy hydroxypropyl sulfonate and benzotriazole-methyl methacrylate as monomers, and the specific preparation method is described in the preparation method of the hydrogenation catalyst film-forming flame retardant.

[0068] The preparation method of the hydrogenation catalyst film-forming flame retardant of this embodiment is the same as that of Example 1, and the only difference is that the mass fractions of the components are different.

[0069] Comparative Example 1 A hydrogenation catalyst film-forming flame retardant, by weight parts, comprising the following components: dodecanol 90 parts, anionic surfactant alkyl sulfonate 5 parts, dispersant higher alcohol 0.5 parts and cosolvent diesel 5 parts.

[0070] Comparative Example 2 A hydrogenation catalyst film-forming flame retardant, by weight parts, comprising the following components: dodecanol 90 parts, 3-aminopropyl triethoxysilane modified silica nanoparticles 1 part, anionic surfactant alkyl sulfonate 5 parts, dispersant higher alcohol 0.5 parts and cosolvent diesel 5 parts.

[0071] Performance evaluation: The hydrogenation catalyst film-forming flame retardants provided by Examples 1-7 and Comparative Examples 1-2 are used for catalyst unloading, and the specific method is as follows:

[0072] Step one, reduce the reactor bed temperature to 350℃ at a speed of 15~20℃ per hour;

[0073] Step two, introduce wax oil into the reactor from the direct current wax oil pipeline at a speed of 50 t / h to replace the residual oil in the reactor, and gradually increase the amount of wax oil to 200 t / h after stabilization, and correspondingly reduce the residual oil to 0 as much as possible, and the reaction system is circulated at 320°C for 18 h, and the wax oil replacement is qualified, and then the reactor temperature is lowered to 290°C at a cooling rate of 15-20°C / h, and the pressure of the reaction system is reduced to 12 MPa at a rate of 1-1.5 MPa / h;

[0074] Step three, introduce diesel oil into the reaction system at a speed of 50 t / h, gradually increase the diesel oil feed amount to 200 t / h, and continue to reduce the reaction temperature to 200°C at a rate of 5°C / h, and the diesel oil replacement is 9 h;

[0075] Step four, when the temperature is reduced to below 200°C and the replacement is qualified (50°C viscosity is less than 12 Cst), inject the fire-retardant composition from the inlet pipeline of the reaction feed pump, the oil (wax oil and diesel oil) replacement time is about 30 hours, the weight percentage of the composition in the oil is 3%, and the oil is a mixture of wax oil and diesel oil in a ratio of 1:50. During the injection process, the reactor bed temperature is reduced from 200°C to about 170°C;

[0076] Step five, after the injection of the fire-retardant composition, the reaction system temperature is maintained at 170°C for 8 hours to close the loop, and the surface of the catalyst is passivated to form a thin film of about 10 μm on the surface of the catalyst;

[0077] Step six, after the oil circulation cooling is stopped, continue to circulate the gas, and at the same time, the oil in the catalyst, the pipeline and the device is blown out; when the reactor bed temperature is reduced to below 50°C, stop the operation of the circulating gas compressor.

[0078] Fire-retardant performance test: after the above-mentioned catalyst treated by unloading agent is wiped with filter paper, it is placed in an infrared oven together with the filter paper, the temperature at which red-brown color appears and smoke begins to appear is observed, and the temperature is rated, 1st grade is temperature less than or equal to 120°C; 2nd grade is temperature greater than 120°C and less than or equal to 140°C; 3rd grade is temperature greater than 140°C and less than or equal to 160°C; 4th grade is temperature greater than 160°C and less than or equal to 180°C; 5th grade is temperature greater than 180°C and less than or equal to 200°C; 6th grade is temperature greater than 200°C and less than or equal to 220°C; 7th grade is temperature greater than 220°C and less than or equal to 240°C; 8th grade is temperature greater than 240°C; the temperature rating results are shown in Table 1.

[0079] Table 1 Fire-retardant performance test results

[0080]

[0081] As can be seen from Table 1, the cross-linked grafted nano-silica is dispersed in the oxygen-containing hydrocarbon to form a nanofluid, which improves the permeability of the film-forming flame retardant, rapidly penetrates into the inside of the caked catalyst, and the sodium allyloxy hydroxypropyl sulfonate, benzotriazole-methyl methacrylate are used as polymerization monomers, the cross-linked grafted modified 3-aminopropyl triethoxysilane modified silica nanoparticles, the sodium allyloxy hydroxypropyl sulfonate can improve the wettability of the nanofluid to the surface of the catalyst, ensure that the film-forming flame retardant uniformly covers the catalyst, realizes more uniform and denser wrapping of the catalyst, and can improve the flame retardant performance.

[0082] Environmental stability test: the catalyst before and after the catalyst is unloaded is placed in light, air, 37℃ conditions for 6h, the temperature rise T0 of the middle part of the catalyst before unloading is tested using a thermometer, and the temperature rise T1 of the middle part of the catalyst after unloading is tested, and the difference T0-T1 between the temperature rises before and after unloading is calculated, and evaluated, wherein 1st is the difference in temperature rise greater than 10℃, 2nd is the difference less than or equal to 10℃ and greater than 8℃, 3rd is the difference less than or equal to 8℃ and greater than 6℃, 4th is the difference less than or equal to 6℃, and the results are shown in Table 2.

[0083] Table 2 Environmental stability test results

[0084]

[0085] As can be seen from Table 2, the film-forming flame retardant of Examples 1-7 can promote the stability of the catalyst under conditions such as air or light, improve the safety of catalyst unloading and catalyst regeneration, and the film-forming flame retardant of Comparative Examples 1-2 has less effect on the stability of the catalyst than Examples 1-7.

[0086] Oil content test: the above catalyst after unloading is extracted with benzene-ethanol, and the change rate of carbon content in the catalyst before and after extraction is calculated as the oil content, wherein the oil content=(carbon content of the catalyst before extraction-carbon content of the catalyst after extraction) / carbon content of the catalyst before extraction x 100%, the oil content is evaluated, 1st is the oil content less than or equal to 2%, 2nd is the oil content greater than 2% and less than or equal to 4%, 3rd is the oil content greater than 4% and less than or equal to 5%, 4th is the oil content greater than 5% and less than or equal to 7%, and 5th is the oil content greater than 7%, and the results are shown in Table 3.

[0087] Table 3 Oil content test results

[0088]

[0089] As can be seen from Table 3, the use of higher aliphatic alcohols containing 12-18 carbon atoms and anionic surfactant alkyl sulfonate other ingredients together makes the oil content of the catalyst less than 2%, which does not affect the activity of the catalyst.

[0090] The above description of the specific embodiments of the present application is not intended to limit the scope of the present application. Various other corresponding changes and modifications according to the technical concept of the present application should be included in the scope of the present application claimed.

Claims

1. A film-forming flame retardant for hydrogenation catalysts, characterized by, By weight parts, including the following components: oxygen-containing hydrocarbon 90~95 parts, crosslinked grafted nano-silica 1~5 parts, anionic surfactant 5~10 parts, dispersant 0.5~1 parts and cosolvent 5~10 parts; The crosslinked grafted nano-silica is obtained by grafting polymer on the surface of 3-aminopropyl triethoxysilane modified silica nanoparticles with sodium allyloxy hydroxypropyl sulfonate and benzotriazole-methyl methacrylate as monomers; The oxygen-containing hydrocarbon is a higher fatty alcohol containing 12~18 carbon atoms; The anionic surfactant is an alkyl sulfonate.

2. The film-forming flame retardant for hydrogenation catalyst according to claim 1, characterized by The dispersant is a higher alcohol, and the cosolvent is diesel oil or kerosene.

3. The process for the preparation of a film-forming flame retardant for hydrogenation catalysts according to claim 1, characterized in that, Including the following steps: S1, 3-aminopropyl triethoxysilane modified silica nanoparticles are added to deionized water, ultrasonic dispersion is uniform, heated to 50~55℃, polymer monomers sodium allyloxy hydroxypropyl sulfonate and benzotriazole-methyl methacrylate are added, then initiator ammonium persulfate is added, continue to stir for 10 min, then continue to react under sealed condition for 4~5h, after the reaction is completed, add acetone to precipitate the precipitate, centrifugal separation of the precipitate, washed and dried to obtain crosslinked grafted nano-silica; S2, oxygen-containing hydrocarbon, crosslinked grafted nano-silica, surfactant and dispersant are added to cosolvent at 60~65℃, mixed and stirred for 30 min to obtain hydrogenation catalyst film forming flame retardant.

4. The process for the preparation of a film of hydrogenation catalyst flame retardant according to claim 3, characterized in that, In step S1, the preparation method of the 3-aminopropyl triethoxysilane modified silica nanoparticles is as follows: nano-silica is added to anhydrous ethanol, stirred and dispersed at room temperature to obtain a nano-silica dispersion liquid; Mix 3-aminopropyl triethoxysilane and water in a volume ratio of 1:2, and stir to obtain a silane coupling agent aqueous solution; Pour the silane coupling agent aqueous solution into the nano-silica dispersion liquid, stir and mix, react at 70~75℃ for 3h, centrifugal separation of the precipitate after the reaction is completed, washed, dried to obtain 3-aminopropyl triethoxysilane modified silica nanoparticles.

5. The process for the preparation of a film of hydrogenation catalyst flame retardant according to claim 4, characterized in that, The solid-liquid ratio of the nano-silica and 3-aminopropyl triethoxysilane is 1g:5mL.

6. The process for the preparation of a film of hydrogenation catalyst flame retardant according to claim 3, characterized in that, In step S1, the preparation method of benzotriazole-methyl methacrylate is as follows: 1-hydroxymethyl benzotriazole, triethylamine and butanone are mixed, methyl methacryloyl chloride butanone solution is slowly added, reacted at 0~10℃ for 2h, then reacted at 22~25℃ for 5h, after the reaction is completed, remove the solid material by filtration, the obtained solution is rotary evaporated, then add ether, then washed with sodium hydroxide solution, washed with distilled water, dried with anhydrous sodium sulfate, remove the solid material, rotary evaporated to obtain benzotriazole-methyl methacrylate.

7. The process for the preparation of a film of hydrogenation catalyst flame retardant according to claim 6, characterized in that, The molar ratio of 1-hydroxymethyl benzotriazole and methyl methacryloyl chloride is 1~1.25:1, and the amount of triethylamine added is 30% of the total molar amount of 1-hydroxymethyl benzotriazole and methyl methacryloyl chloride.

8. The process for the preparation of a film of hydrogenation catalyst flame retardant according to claim 3, characterized in that, In step S1, the molar ratio of the sodium allyloxyhydroxypropyl sulfonate and the benzotriazole-methyl methacrylate is 1:1~1.02, the mass ratio of the 3-aminopropyl triethoxysilane modified silica nanoparticles to the total mass of the sodium allyloxyhydroxypropyl sulfonate and the benzotriazole-methyl methacrylate is 1:5, and the mass of the initiator ammonium persulfate is 20% of the total mass of the sodium allyloxyhydroxypropyl sulfonate and the benzotriazole-methyl methacrylate.

9. Use of the hydrogenation catalyst film forming flame retardant according to claim 1, characterized in that, The catalyst is applied to catalyst protection when a hydrogenation device is unloaded, and the hydrogenation device is any one of a fixed bed residual oil hydrogenation device, a fixed bed wax oil hydrogenation device, a fixed bed hydrocracking device, a fixed bed diesel oil hydrogenation device, a fixed bed diesel oil reforming device, a fixed bed kerosene hydrogenation device, a fixed bed gasoline hydrogenation device, a fixed bed gasoline hydrogenation reforming device, a fixed bed naphtha hydrogenation device, and a fixed bed coal tar hydrogenation device.

Citation Information

Patent Citations

  • Using method of SHYZ-1 hydrogenation catalyst fire retardant

    CN109135810A

  • Flame-retardant composition for hydrogenation catalysis and use method of flame-retardant composition

    CN112871219A